Data Envelopment Analysis A Handbook of Models and Methods - Zhu, Joe.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2015)
This handbook represents a milestone in the progression of Data Envelopment Analysis (DEA). Written by experts who are often major contributors to DEA theory, it includes a collection of chapters that represent the current state-of-the-art in DEA research. Topics include distance functions and their value duals, cross-efficiency measures in DEA, integer DEA, weight restrictions and production trade-offs, facet analysis in DEA, scale elasticity, benchmarking and context-dependent DEA, fuzzy DEA, non-homogenous units, partial input-output relations, super efficiency, treatment of undesirable measures, translation invariance, stochastic nonparametric envelopment of data, and global frontier index. Focusing only on new models/approaches of DEA, the book includes contributions from Juan Aparicio, Mette Asmild, Yao Chen, Wade D. Cook, Juan Du, Rolf Färe, Julie Harrison, Raha Imanirad, Andrew Johnson, Chiang Kao, Abolfazl Keshvari, Timo Kuosmanen, Sungmook Lim, Wenbin Liu, Dimitri Margaritis, Reza Kazemi Matin, Ole B. Olesen, Jesus T. Pastor, Niels Chr. Petersen, Victor V. Podinovski, Paul Rouse, Antti Saastamoinen, Biresh K. Sahoo, Kaoru Tone, and Zhongbao Zhou.
Distance Functions in Primal and Dual Spaces -- DEA Cross Efficiency -- DEA Cross Efficiency Under Variable Returns to Scale -- Discrete and Integer Valued Inputs and Outputs in Data Envelopnebt Analysis -- DEA Models with Production Trade-offs and Weight Restrictions -- Facet Analysis in Data Envelopment Analysis -- Stochastic Nonparametric Approach to Efficiency Analysis: A Unified Framework -- Translation Invariance in Data Envelopment Analysis -- Scale Elasticity in Non-parametric DEA Approach -- DEA Based Benchmarking Models -- Data Envelopment Analysis with Non-Homogeneous DMUs -- Efficiency Measurement in Data Envelopment Analysis with Fuzzy Data -- Partial Input to Output Impacts in DEA: Production Considerations and Resource Sharing Among Business Sub-Units -- Super-efficiency in Data Envelopment Analysis -- DEA Models with Undesirable Inputs -- Frontier Differences and the Global Malmquist Index.
Keywords: Operations research; Decision making; Management science; Industrial engineering; Production engineering; Operations Research/Decision Theory; Operations Research, Management Science; Industrial and Production Engineering